Family building in the thought of the Holy Prophet (PBUH ) - faisal, Professor Dr. Mokhalad adhyab; Abdulrazzaq, Ahmed Abdulkareem (Thi Qar Arts Journal, 2022)
The Holy Prophet, peace and blessings be upon him, sought to organize the family as it is the basic building block of the society, which with its righteousness fixes the state of the society. The family is based on chastity, love, respect, honesty, tolerance and cooperation.In the research, we dealt with several topics, including marriage as a divine Sunnah that is linked to the nature and existence of man, and how the Holy Prophet (PBUH) called for it and what are the goals behind it. We also dealt with the rights of spouses and how to preserve the sacred bond between them through the commandments of the Holy Prophet (PBUH).Then we mentioned the upbringing of children and the matters that interfere with it from the first moments of choosing a wife and during the first years of their lives until the age of puberty.